2019
DOI: 10.1371/journal.pone.0214838
|View full text |Cite|
|
Sign up to set email alerts
|

Death of a close friend: Short and long-term impacts on physical, psychological and social well-being

Abstract: This paper reports the impact of a major life event–death–on the physical, psychological and social well-being of the deceased’s close friends. We utilised data from a large longitudinal survey covering a period of 14 years (2002–2015) consisting a cohort of 26,515 individuals in Australia, of whom 9,586 had experienced the death of at least one close friend. This longitudinal cohort dataset comprises responses to the SF-36 (health related quality of life measure) and allowed for analysis of the short and long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 73 publications
1
38
0
Order By: Relevance
“…This was explained by not having fun in social settings anymore, not wanting to be parts of larger groups, and experiencing reminders of their friends. Being socially inactive can however prolong the deterioration in physical and mental health after a loss (30). The internal structure and distinctiveness of CG in adolescents may bear resemblance to what is known from adult populations, but focus on depressive and anxious symptoms in bereavement-related distress might overlook that other patterns of complications may occur in bereaved adolescents (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was explained by not having fun in social settings anymore, not wanting to be parts of larger groups, and experiencing reminders of their friends. Being socially inactive can however prolong the deterioration in physical and mental health after a loss (30). The internal structure and distinctiveness of CG in adolescents may bear resemblance to what is known from adult populations, but focus on depressive and anxious symptoms in bereavement-related distress might overlook that other patterns of complications may occur in bereaved adolescents (6).…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by: (a) adolescents idealize their retrospective accounts; (b) as they move beyond the initial grief, they realize how upset they were initially, and appraise and report the past grief more accurately; and (c) the memory of the past grief is stronger in comparison to present grief. Liu and colleagues (30) found that loss of a friend caused signi cant adverse physical and psychological wellbeing, poorer mental health and impairment in social functioning, which occur up to four years following bereavement. Having to go back to reality, both to work or school or socially, often without being able to perform or function the way they wanted and expected, was di cult for many of the bereaved friends in our sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that post-DOCO functioning may be supported through the investment in and defense of valued worldviews, self-esteem, and identities. Indeed, previous research on grief and bereavement suggest that those who have endured the death of someone close can benefit from engaging with broader social groups and reconstructing a sense of meaning in life (e.g., Liu et al, 2019;Neimeyer et al, 2006;Pressman & Bonanno, 2007). Moreover, some work has found that self-enhancement helps to support psychological adjustment following potentially traumatic experiences, including the death of a close other (Gupta & Bonanno, 2010;Yan & Bonanno, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For the present study, we anticipate somewhat lower effect sizes as we study comparatively less close relationship partners. Evidence is scarce but a recent study has revealed effects of friend loss of .11 for life satisfaction after 10-12 months (Liu et al, 2019).…”
Section: Power Analysismentioning
confidence: 99%